Commerce adoption among businesses in Indonesia - Mahomed, Anuar Shah Bali; Sheikh Mokhtar, Siti Salwa; Burda, Agustian; Maronrong, Ridwan; Reza, Syahrul (Fakulti Ekonomi dan Pengurusan, Universiti Putra Malaysia, 2023)
Despite the substantial engagement of Indonesian consumers in e-commerce, there remains a noteworthy disparity in the adoption of e-commerce among businesses. By integrating the Technology Acceptance Model (TAM) and the Technology-Organisation-Environment (TOE) framework, the aim of this research was to identify the direct and indirect influences of selected factors on e-commerce adoption intention among businesses in Indonesia. Self administered questionnaires were distributed to respondents from the manufacturing and service industries for data collection. The results of structural equation modelling analysis revealed that TOE factors directly influence the TAM factors of perceived usefulness, perceived ease of use, and adoption intention towards e-commerce in Indonesia. Additionally, perceived ease of use was found to mediate the effect of the TOE factors on businesses’ adoption intention